(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Electronic waste poses a major menace to ecosystems owing to the toxic properties of materials used for the manufacture of electronic goods. In this present study, the toxicity of lithium battery waste on invertebrates, snails (Archachatina marginata) and earthworms (Apporrectodeal longa) were evaluated using appropriate concentrations of toxicant. The physicochemical and heavy metal analysis of the toxicant was carried out according to the method of APHA (2008). The standard protocol obtained from the Organization for Economic Cooperation and Development (OECD) and the protocol obtained from the International Organization for Standardization (ISO) were adopted for the 14-day exposure to varying concentrations of the toxicant (0.3125, 0.625, 1.25, 2.5 and 5.0 mg/kg) for earthworm and (3.125,6.25, 12.5, 25 and 50 mg/kg) for snail respectively. The pH, Electrical conductivity. Total dissolved solids, Lithium, cadmium and mercury results of the toxicant were (2.6, 13500, 8640, 36.60, 2.03 and 10.48mg/L) respectively. The result also shows an increased in the mortality of test organisms with increase in toxicant concentration. LC50, LOEC, NOEC, TUc and TUa with exposure time for snails and earthworms were (1.05, 0.86,0.77,94.88, 129.87 mg/kg) and (0.68, 0.41,0.31, 147.06, 322.58.mg/kg), respectively. The study established that the toxicant (lithium battery) is considered a high risk to animals, plants and the environment as it adversely affects soil invertebrates which bring about soil fertility if not properly disposed of.